Innovative Learning Design Using the Traditional Bakiak Game to Optimize Interpersonal Intelligence in Early Childhood: A Pre-Experimental Study - Riza Oktariana; Helnita Helnita; Raudha Meutia; Fitriah Hayati; Nurummi Salsabila; Arifa Yasira; Amelia Putri (International Journal of Educational Narratives, 2026)
Background. Interpersonal intelligence is a critical yet often overlooked dimension of early childhood development, as many early childhood education practices continue to emphasize academic readiness over social and interpersonal skills. Traditional games such as bakiak, which require coordination and communication among children, offer a culturally grounded medium for fostering this intelligence, yet their use in early childhood education remains limited. Purpose. This study aims to assess how an innovative learning design based on the traditional bakiak game influences children’s interpersonal intelligence. Method. This research employed a quantitative approach using a one-group pretest-posttest design, conducted at TK Khairani Aceh Besar in Lubok Batee Village, Ingin Jaya District, Aceh Besar Regency, from January 15 to April 15, 2026. The participants were 44 children from Group B, selected through purposive sampling. Data were collected using a structured observation checklist and a Likert-scale rating instrument covering cooperation, communication, and empathy, and analyzed using descriptive statistics and a paired sample t-test. Results. The mean interpersonal intelligence score increased from 56.0 (pretest) to 82.7 (posttest), a gain of 26.7 points, with a moderate-to-high normalized gain score (g = 0.61) and an average improvement of 47.6%. Conclusion. The traditional bakiak game positively and significantly enhances the interpersonal intelligence of early childhood learners, particularly in cooperation, communication, and empathy, supporting its integration as a culturally relevant learning strategy in early childhood education.